2020
DOI: 10.1177/0146167220911496
|View full text |Cite
|
Sign up to set email alerts
|

Dehumanizing Prisoners: Remaining Sentence Duration Predicts the Ascription of Mind to Prisoners

Abstract: We tested the novel hypothesis that the dehumanization of prisoners varies as a function of how soon they will be released from prison. Seven studies indicate that people ascribe soon-to-be-released prisoners greater mental sophistication than those with more time to serve, all other things being equal. Studies 3 to 6 indicate that these effects are mediated by perceptions that imprisonment has served the functions of rehabilitation, retribution, and future deterrence. Finally, Study 7 demonstrates that belief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This is especially true when these individuals have committed violent or sex crimes (Bastian, Denson, & Haslam, 2013;Viki, Fullerton, Raggett, Tait, & Wiltshire, 2012). Deska et al (2020) found that the perception of prisoners as human increases as they get closer to their release date, implying that prisoners are devoid of human features while incarcerated and that the criminal justice system has done its job of rehabilitating offenders.…”
Section: Salient Target Populations and The Subcategorization Of Devimentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially true when these individuals have committed violent or sex crimes (Bastian, Denson, & Haslam, 2013;Viki, Fullerton, Raggett, Tait, & Wiltshire, 2012). Deska et al (2020) found that the perception of prisoners as human increases as they get closer to their release date, implying that prisoners are devoid of human features while incarcerated and that the criminal justice system has done its job of rehabilitating offenders.…”
Section: Salient Target Populations and The Subcategorization Of Devimentioning
confidence: 99%
“…Drawing primarily on the public policy literature, this essay presents the concept of salient target populations (Bosak, Asbrock, & Meyer, 2018;Ingram, Schneider, & DeLeon, 2007;Schneider & Ingram, 1993, 1997. It is argued herein that early release policies depend on the salience of the inmate population (Deska, Almaraz, & Hugenberg, 2020;Vasiljevic & Viki, 2014). According to Ingram et al (2007), "policies often subdivide target populations, creaming off the most positively constructed of dependent and deviant groups and affording them better treatment" (p. 104).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, longer and harsher prison sentences can increase the possibility of a personality change of a prisoner. [2,3] To an inmate, contact with the outside world is of great importance. Being in a closed institution is very inconvenient and leads to people having psychological difficulties and penitentiary stress.…”
Section: Introductionmentioning
confidence: 99%
“…Within the penal system, dehumanization literature has called for more humanistic treatment by officers (Guenther, 2012;Kelso, 2014). Empirically, dehumanization's impact extends beyond confinement into courtrooms-participants determined incarcerated people with dehumanizing descriptions (compared to control incarcerated people) should receive harsher punishments and judged them to have reduced mental sophistication (Deska et al, 2018(Deska et al, , 2020. Within carceral institutions, officer's experiences of organizational dehumanization (i.e., feeling less than human as a staff member) have been cross-sectionally associated with perpetuating depersonalization and dehumanization on to incarcerated persons (Stinglhamber et al, 2022).…”
mentioning
confidence: 99%